Effects of Science Process-Based Method on Creativity among Secondary School Biology Students with Varied Abilities in Zaria, Nigeria - ANYIFITE, Sylvester Azubuike (Ilorin Journal of Education, 2024)
The study, focused on the Impact of Science Process-Based Approach on Creativity among Secondary School Biology Students with Varied Abilities in Zaria, Nigeria," it aimed to determine the effect of teaching methods on students’ creativity. Two research questions and two null hypotheses were formulated and tested at a significance level of P≤0.05. A pretest and posttest quasi-experimental design with a control group was employed, involving 133 SSII students from two coeducational secondary schools in Zaria. The experimental group received instruction on living concepts in Biology using Science Process-Based Approach (SPBA), while the control group experienced the Lecture Method. The Creativity Test Questionnaire (CTQ) served as the validated instrument for data collection. Statistical analyses included mean rank, standard deviation, one-way analysis of variance (ANOVA), analysis of covariance (ANCOVA), and Kruskal Wallis. The study findings revealed that students taught using SPBA exhibited significant differences in creativity traits, favoring the high experimental group over the lecture method, and male and female students taught using SPBA performed significantly better in creativity traits, favoring the high female experimental group over the lecture method. In light of these results, the study recommends organizing SPBA training for Biology teachers through workshops to equip them for integrating this approach into lessons, particularly in teaching specific Biology concepts, to enhance students’ creativity.